2001
DOI: 10.1159/000055142
|View full text |Cite
|
Sign up to set email alerts
|

Coincidence of Nutritional Habits and Esophageal Cancer in Germany

Abstract: Introduction: The incidence rates for adenocarcinoma (AC) of the esophagus have risen rapidly in Western nations, whereas the incidence rates for esophageal squamous cell carcinoma (SCC) have remained nearly stable. There are studies about body mass index, smoking, alcohol, and development of AC or SCC. The aim of this study was to evaluate differences in nutritional habits of patients with AC or SCC compared with the population in Cologne. Patients and Methods: From January 1, 1997 to December 31, 1998, 85 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 26 publications
2
41
0
2
Order By: Relevance
“…12,16,30,31 In contrast, the association between fruit and vegetable intake and EAC risk has been inconsistent. Some previous studies observed significant Adjusted for sex, age at entry into cohort, BMI, education, alcohol intake, cigarette-smoke-dose, vigorous physical activity, usual activity throughout the day, and total energy.- inverse associations with fruit intake, 33,34 vegetable intake [35][36][37] and combined fruit and vegetable intake. 15 Other studies observed suggestive but nonsignificant inverse associations with fruit [35][36][37][38] and vegetables.…”
Section: Discussionmentioning
confidence: 91%
“…12,16,30,31 In contrast, the association between fruit and vegetable intake and EAC risk has been inconsistent. Some previous studies observed significant Adjusted for sex, age at entry into cohort, BMI, education, alcohol intake, cigarette-smoke-dose, vigorous physical activity, usual activity throughout the day, and total energy.- inverse associations with fruit intake, 33,34 vegetable intake [35][36][37] and combined fruit and vegetable intake. 15 Other studies observed suggestive but nonsignificant inverse associations with fruit [35][36][37][38] and vegetables.…”
Section: Discussionmentioning
confidence: 91%
“…Besides Plummer-Vinson syndrome and scleroderma, achalasia and chronic mucosal irritation are also known risk factors. Additional risk factors for the development of ESCC are nutritional factors like the presence of nitrosamines in the food and vitamin deficiency [2]. Contrary to ESCC the most important risk factor for the development of EAC is the presence of columnar-lined esophagus (CLE), also known as Barrett's esophagus.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Chronic gastro-esophageal reflux leading to metaplasia and Barrett esophagus is regarded as major risk factor [22]. Additional etiological agents are in discussion [19,23,36,43].…”
Section: Introductionmentioning
confidence: 99%